Long noncoding RNA MALAT1 acts as a potential biomarker in cancer diagnosis and detection: a meta-analysis. (18th December 2018) - Mei, Hongbing; Liu, Yuhan; Zhou, Qun; Hu, Kun; Liu, Yuchen
Aim: it has been reported that metastasis-associated lung adenocarcinoma transcript 1 is abnormally expressed in various cancers.Methods: eligible studies fulfilling the search criteria were selected from the online databases. Statistical analysis was performed based on the platforms of STATA 14.0.Results: 12 studies were included in this study comprising 741 cases and 794 controls. The pooled results were shown as follows: sensitivity, 0.74 (95% CI: 0.64–0.82), specificity, 0.83 (95% CI: 0.75–0.88), positive likelihood ratio (PLR), 4.2 (95% CI: 3.00–5.90), negative likelihood, 0.32 (95% CI: 0.23–0.43), diagnostic odds ratio, 13 (95%CI: 8.00–21.00) and area under the curve, 0.85 (95%CI: 0.82–0.88). Deeks' funnel plot asymmetry test (p = 0.70) suggested no potential publication bias.Conclusion: long noncoding RNA Metastasis-associated lung adenocarcinoma transcript 1 might be a usable biomarker for cancer diagnosis and detection.